HIV Antibody Seroprevalence and Determinants Amongst Antenatal Clients in a Tertiary Hospital in the Niger Delta - E.L., Kotingo; D.O.B., Allagoa (European Scientific Journal, ESJ, 2018)
Background: The pandemicity of the human immunodeficiency virus (HIV) has continued to be a ‘medical quagmire,’ one of the most serious global catastrophe and public health problem that plagues the world today. Objectives: To determine the seroprevalence and clinico-epidemiological correlates of HIV infection in pregnancy. Methodology: This is a descriptive cross sectional study. Two hundred and twenty (220) consecutive healthy pregnant women attending the antenatal booking clinic of the hospital who met the inclusion criteria were recruited. Data was collected via a questionnaire. Data entry and analysis was done using SPSS (statistical package forsocial sciences) 22 statistical package (SPSS Inc., Illinois, U.S.A). P value less than 0.05 was taken as being significant. Results: Of the 220 women, 4.6% (n=10) were seropositive for HIV antibodies. Multiple sexual partners was the significant risk factors for HIV seropositivity (p<0.05). There was no significant association with respect to tattoo/scarification marks, female circumcision, previous blood transfusion, intravenous drug abuse or sharing of sharps, previous surgery, episiotomies or dilatation and curettage (p>0.05). Conclusion: The high endemicity of HIV infection in this study justifies the need for routine screening in pregnancy to identify and institute treatment of the infection promptly as this will reduce the mother to child transmission of the virus. Sex education on the dangers of multiple sexual partners or sexual promiscuity, availability of barrier methods of contraception and patronage, more efforts/interventions by relevant agencies, high sense of vigilance amongst others are very vital to curtailing this global pandemic in our society.